The Effectiveness of Ministerial Regulation No. 6 of 2023 on Gender Equality in Legislation and Legal Instruments for Female Coffee Farmers in Tirtoyudo Village - Wahyudi, Fidela Dzatadini; Ariani, Relys Sandi; Zulfaida, Arini (Universitas Kristen Cipta Wacana, 2025)
Ministerial Regulation PPPA No. 6 of 2023 concerning Gender Equality Parameters in Legislation and other Legal Instruments, which is normatively expected to eliminate existing gender inequality in the state, is not necessarily effective when implemented at the local agrarian community level. The inherent masculinity of patriarchal culture in coffee plantations still makes women coffee farmers have unequal access and control with male coffee farmers. This research examines the effectiveness of Permen PPPA No. 6 of 2023 in the context of local agrarian communities, namely, women coffee farmers in Tirtoyudo Village, Malang Regency. This research uses a juridical-sociological approach with Lawrence Friedman's theory of legal effectiveness. The results of this study show that the implementation of Permen PPPA No. 6 of 2023 is not maximally effective due to the patriarchal culture that is strongly embedded in the community. The lack of gender awareness in the coffee farming community is a major obstacle in the realization of gender equality as regulated in Permen PPPA No. 6 of 2023. Formal recognition alone does not automatically result in equality to the substantive level. So from this research, there is still a gap between legal norms and social reality.